SEMIOTIC ISSUES OF WORD NOMEMA - M. Rahimova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article is related to the semiotic aspect of linguistics, in which the symbolic status of the word is analyzed. It is also suggested that there should be a field of nomemology that studies the formation of nomema.